IMPLEMENTASI DSS MENGGUNAKAN METODE PROFILE MATCHING DALAM PENILAIAN KINERJA KARYAWAN PADA CV. INSYA EVERYTHING - Mesra Betty Yel; Heny Nengsih (CKI ON SPOT, 2021)
Decision Support System Information is a system that can assist managers in making decisions based on criteria that have been determined by the company. Decision Support Systems assist in the assessment process so that there is no subjective judgment in decision making. Assessment based on predetermined criteria is expected to determine which employees are entitled to the right position according to their achievement. Many methods can be used in the creation of a DSS system. One method that can be used in making a decision support system is the Profile Matching method. It is hoped that the application of the profile matching method in the decision-making system can help the process of evaluating employee performance effectively and accurately so that the level of human resources can be maintained and improved. The result of the calculation process using the profile matching method is the value that is ranked based on the largest value. The results of this ranking value will be used as a reference in helping managers to make decisions. The software used in making this decision support system application is the PHP programming language with the MySQL database.